Pengaruh Ukuran Perusahaan, Umur Perusahaan, Diversifikasi Produk Dan Return On Assets Terhadap Pengungkapan Akuntansi Sumber Daya Manusia (Studi Pada Perusahaan Perbankan Dan Asuransi Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-1014) - Setiawan, Hendrik; , Drs. Wahyono, Ak, MA (2016)
The objective is to determine the effect of the company size, company age, diversification of products and return on assets on the human resources accounting disclousure in the banking and insurance companies listed on the Stock Exchange. This research uses a quantitative approach. The data used in this study is the annual financial report banking and insurance companies listed on the Stock Exchange in 2011-2014. The sample used in this study are 132 companies. This study uses secondary data obtained through ICMD quantitative and summary financial statements listed on the Stock Exchange.. Data analysis tool used in this research is multiple linear regression. The results showed that company size does not effect on the accounting disclosure of human resources. Age effect on the company's human resource accounting, disclosure product diversification has no effect on the disclosure of accounting human resources. Return on assets affect the accounting disclosure of human resources.